PRÁTICAS DE LABORATÓRIO - O ELEVADOR HIDRÁULICO - Marcelo Alves Barros; Adriel Antônio Farias; Amarildo Rosa; Ana Paula Giacomassi; Fabiana Ribeiro de Almeida; Fábio Henrique Hirata; Fábio Ramos da Silva; Mônica Bordim Sanches; Mônica Yara Arroteia; Roberto Gonçalves Barbosa (Arquivos do Mudi, 2013)
Os autores apresentam um esperimento que simila um elevador hidráulico.